Peran Penyaluran Kredit Perbankan kepada Sektor Prioritas dalam Mendorong Pemulihan Ekonomi di Pulau Sumatera - Utami, Ni Putu Meiling; Ni Nyoman Dian Sudewi; Ni Ketut Ping Purnama Sari; Ica Rika Candraningrat (Lembaga Pengembangan Kinerja Dosen, 2025)
The financial sector plays an important role in promoting Indonesia's economic recovery. This study was conducted to determine the effect of credit to priority sectors on economic growth on the island of Sumatera. The data analysis technique used is dynamic panel data regression analysis with the system-GMM approach. The results of this study indicate that credit for the agricultural, forestry, and fishery sectors; manufacturing sector; the accommodation and food and drink provision sector can increase economic growth on the island of Sumatera, while the construction sector credit; wholesale and retail trade sector; and the transportation and warehousing sectors have a negative influence on economic growth. This shows that the credit of the banking sector has a positive and negative influence on economic growth on the island of Sumatera. Therefore, banks and the government are expected to increase financial literacy to the community and improve internet facilities, especially in rural areas.